PERANCANGAN SISTEM INFORMASI PENJUALAN PADA CV. SINAR CREATION BERBASIS WEB - Marpaung, Nellys Erlyta; Harianja, Andy Paul (KAKIFIKOM : Kumpulan Artikel Karya Ilmiah Fakultas Ilmu Komputer, 2021)
CV. Sinar Creation is a place to produce printing products in the advertising sector that focuses on service and quality of goods produced well. In this final project, design a web-based sales information system for CV. SINAR CREATION in marketing all information about its products through the media website, so that finally this website is expected to increase sales efficiency in the business world. To support system development, researchers use the PHP and MySQL programming languages as their databases and on this website it is hoped that the sales of this product will be better for the company itself, because this website is equipped with proof of payment which is more efficient and accurate for this company.